Shifts in predator behaviour following climate induced disturbance on coral reefs. Issue 1989 (21st December 2022) - Rotjan, Randi D.; Ray, Nicholas E.; Cole, Ingrid; Castro, Kurt G.; Kennedy, Brian R. C.; Barbasch, Tina; Lesneski, Kathryn C.; Lord, Karina Scavo; Bhardwaj, Anjali; Edens, Madeleine; Karageorge, Ioanna; Klawon, Caitlynn; et al.
Abstract : Coral reefs are increasingly ecologically destabilized across the globe due to climate change. Behavioural plasticity in corallivore behaviour and short-term trophic ecology in response to bleaching events may influence the extent and severity of coral bleaching and subsequent recovery potential, yet our understanding of these interactions in situ remains unclear. Here, we investigated interactions between corallivory and coral bleaching during a severe high thermal event (10.3-degree heating weeks) in Belize. We found that parrotfish changed their grazing behaviour in response to bleaching by selectively avoiding bleached Orbicella spp. colonies regardless of bleaching severity or coral size. For bleached corals, we hypothesize that this short-term respite from corallivory may temporarily buffer coral energy budgets by not redirecting energetic resources to wound healing, and may therefore enable compensatory nutrient acquisition. However, colonies that had previously been heavily grazed were also more susceptible to bleaching, which is likely to increase mortality risk. Thus, short-term respite from corallivory during bleaching may not be sufficient to functionally rescue corals during prolonged bleaching. Such pairwise interactions and behavioural shifts in response to disturbance may appear small scale and short term, but have the potential to fundamentally alter ecological outcomes, especially in already-degraded ecosystems that are vulnerable and sensitive to change.